Preliminary exploration of a computerized cognitive battery and comparison with traditional testing in patients with high-grade glioma. Issue 1 (21st May 2018) - Cerhan, Jane H; Caine, Chip; Anderson, S Keith; Johnson, Derek R; Lachance, Daniel H; Yan, Elizabeth; Brown, Paul D
Abstract: Background: Cognitive function is an important outcome measure in many brain tumor clinical trials, and investigators are interested in employing the most efficient methods of cognitive assessment for this purpose. Computerized testing can be appealing because of the perceived ease of use and electronic data generated. Traditional tests may have the advantage of accumulated validity evidence and comparability across historic trials. Methods: We evaluated feasibility of a Cogstate battery in 39 patients with high-grade glioma, and compared it with a commonly used paper-and-pencil battery. Results: Both batteries were well tolerated and rated equally likeable. Correlations between the batteries were low to low-moderate. More patients showed impairment at baseline and decline across trials on traditional tests. Conclusions: Both batteries were well tolerated, but the most complicated tasks (from both batteries) could not be completed by all subjects. Preliminary validity evidence for the Cogstate tasks was mixed, but a larger sample is needed.